Genetic Improvement of Arundo donax L.: Opportunities and Challenges - Danelli, Tommaso (Plants (Basel), 2020)
Arundo donax L., the giant reed—being a long-duration, low-cost, non-food energy crop able to grow in marginal lands—has emerged as a potential alternative to produce biomass for both energy production, with low carbon emissions, and industrial bioproducts. In recent years, pioneering efforts have been made to genetically improve this very promising energy crop. This review analyses the recent advances and challenges encountered in using clonal selection, mutagenesis/somaclonal variation and transgenesis/genome editing. Attempts to improve crop yield, in vitro propagation efficiency, salt and heavy metal tolerance by clonal selection were carried out, although limited by the species’ low genetic diversity and availability of mutants. Mutagenesis and somaclonal variation have also been attempted on this species; however, since Arundo donax is polyploid, it is very difficult to induce and select promising mutations. In more recent years, genomics and transcriptomics data are becoming available in Arundo, closing the gap to make possible the genetic manipulation of this energy crop in the near future. The challenge will regard the functional characterization of the genes/sequences generated by genomic sequencing and transcriptomic analysis in a complex polyploid genome.